Airway tight junctions as targets of viral infections: Tight Junctions and Viral Infections. Issue 2 (3rd April 2021) - Linfield, Debra T.; Raduka, Andjela; Aghapour, Mahyar; Rezaee, Fariba
ABSTRACT: The apical junctional complexes (AJCs) of airway epithelial cells are a key component of the innate immune system by creating barriers to pathogens, inhaled allergens, and environmental particles. AJCs form between adjacent cells and consist of tight junctions (TJs) and adherens junctions (AJs). Respiratory viruses have been shown to target various components of the AJCs, leading to airway epithelial barrier dysfunction by different mechanisms. Virus-induced epithelial permeability may allow for allergens and bacterial pathogens to subsequently invade. In this review, we discuss the pathophysiologic mechanisms leading to disruption of AJCs and the potential ensuing ramifications. We focus on the following viruses that affect the pulmonary system: respiratory syncytial virus, rhinovirus, influenza viruses, immunodeficiency virus, and other viruses such as coxsackievirus, adenovirus, coronaviruses, measles, parainfluenza virus, bocavirus, and vaccinia virus. Understanding the mechanisms by which viruses target the AJC and impair barrier function may help design therapeutic innovations to treat these infections.